English Standar Kompetensi, Kompetensi Dasar, & Ujian Nasional of SMA in Revised Bloom`s Taxonomy - Putri Kamalia Hakim (Script Journal: Journal of Linguistics and English Teaching, 2017)
Abstract: This study was conducted to investigate the coverage of Revised Bloom’s taxonomy in the English Standar Kompetensi (SK), Kompetensi Dasar (KD) and the English test items of Ujian Nasional for SMA. Content analysis method was chosen as the research design for this study. The writer analyzed the data by categorizing the verbs and the nouns of the data in relation to the categories and dimension of Revised Bloom’s Taxonomy. The results of this study revealed that 53% of SKs and KDs cover Understand category and the rest cover Analyze category. All of the SKs and KDs cover conceptual knowledge and other knowledge dimensions are not covered. Moreover, the coverage of Revised Bloom’s Taxonomy in English test items of Ujian Nasional for SMA is not aligned with the coverage of Revised Bloom’s Taxonomy in English SK and KD. The SKs and KDs only cover Remember, Understand, Apply and Analyze categories while the test items were associated with Remember, Understand, Apply, Analyze, and Evaluate categories. More than 90% of English test items of Ujian Nasional for SMA only covered low order of cognitive categories (Remember, Understand, and Apply). Most of the test items covered factual knowledge and the rest of them covered conceptual knowledge and none of them covered procedural and metacognitive knowledge.